Chaos on CatNet - Kritzer, Naomi (Tor Teen, 2021)
Steph and her mom settle in Minneapolis where Steph befriends Nell, whose mother and girlfriend are missing, and together with the help of ChesireCat they work to find Nell's missing loved ones and end up uncovering a nefarious AI hacking into social networks and chats to instigate paranoia and violence in the real world.